Feasibility analysis of road maintenance with floor management software: application of the hdm-4 on the BR 010 / MA highway - Magalhães Ramos, Marlice; Cavaignac, André Luís de oliveira; Mayor Gonzalez, José Manuel (Brazilian Journal of Production Engineering, 2020)
The best moment for interventions, with a rational selection process for priority stretches, generates an effective investment allocation, prioritizing preventive maintenance and small corrections and bringing benefits to the whole society. For this purpose, the Pavement Management System (PMS) was used as a tool to better monitor and manage resources for the road infrastructure, especially on the Federal Highway BR-010 / MA, segment 260.8 km to km 319.8. Anomalies existing in the segment under study were identified, reporting the causes of their appearance. Then, through the SGP, a solution was proposed to correct the problems encountered, seeking the best cost benefit. As for the pavement situation, it was observed that the fact of having been without a maintenance contract for five months, during the rainy season in the region, accelerated the deterioration process, proving the need for a continued investment policy and an effective management of resources public and corroborating the hypothesis of PMS implantation to have interferences at the right time, generating less expense to public coffers, road users and final consumers by reducing the cost of freight. In addition to less impact on the environment. The alternative that presents the best Internal Rate of Return - IRR (Internal Rate of Return) is CREMA 2. In the first stretch, the IRR is 288.2, 68% higher than Restoration and 107% higher than Reconstruction. In the second section, the IRR is 388.6, 72% higher than Restoration and 198% higher than Reconstruction.
Keywords: Highways; Management; Conservation; Maintenance.